Rancang Bangun Jig and Fixture Pembengkok Pipa Baja ST37 untuk Rangka Kursi Kelas - Wawan Kurniawan; Erwanto Erwanto; Nanda Pranandita (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Designing a pipe bending jig and fixture by applying the stages of the VDI 2222 method, so that a design suitable for the production process of class chairs is obtained. At this stage, written data regarding the bending of ST37 pipes and research results using the VDI 2222 research method are collected from reputable sources such as journals, books, research reports, scientific papers, and articles. From the bending results, it can be concluded that the ST37 pipe responds quite well when bent using this tool, producing good bends and only experiencing slight ovalization compared to other pipes. Therefore, this 1.4 mm diameter ST37 pipe becomes the best product choice compared to other ½-inch pipes. Based on the analysis of the tool I designed and built, it can be concluded that the tool using the VDI 2222 method is capable of bending ST37 pipe with a diameter of 1.4 mm shows quite good bending results, only experiencing slight ovalization.